Capacity Building Indicators for Faculty Development Programs - Kiran Fatima Bana; Talea Hoor; Kulsoom Fatima Rizvi (Journal of Bahria University Medical and Dental College, 2021)
Capacity development targets the changes occurs in human behavior in response to learn any new skills, knowledge, behavior and values overtime within complex organization setting. This development process indicates the progressive readiness of human resource to perform in complex environment. Similarly, this growth process of individual would reflect when dealing with others.